Faktor-faktor yang mempengaruhi niat kewirausahaan - Doddy Adhimursandi (KINERJA, 2016)
Instill the entrepreneurial spirit is not an easy thing to do because there are several factors that must be considered in growing interest in entrepreneurship. Some of the factors in question are a factor that comes from outside and inside the private student among other entrepreneurial traits and skills as well as contextual factors. Each of these factors consists of several indicators that are measured using a Likert scale of 1 to 5. Population and sample in this research is the students of S1 Faculty of Economics and Business, University Mulawarman Samarinda ever take entrepreneurship courses or have completed entrepreneurship training both inside and outside the college campus. Population and sample in this study were 98 students, in order to qualify for the analysis of the data used in this research is using Structural Equation Model PLS. The results showed that the traits and contextual variables entrepreneurial no significant effect on entrepreneurial intentions, while variable entrepreneurial skills significantly influence entrepreneurial interests.